SOCIALIZATION TO MINIMIZE THE WHITE GROUP IN THE 2024 GENERAL ELECTION IN KUALA DUA VILLAGE KUBU RAYA REGENCY - Bakran Suni; Syarif Usmulyadi; Asmadi; Adibrata Iriansyah (UPT. PKM UB, 2024)
The 2024 General Election for Presidential, Vice Presidential, and Legislative Candidates on February 14 and November for Regional Heads are very vulnerable to groups of white groups. Of course, this will result in low public participation in the 2024 elections. This Community Service aims to increase community political participation by minimizing abstentions in elections based on first-time voters and voters who have repeatedly participated in the election of legislative candidates, executive candidates, and regional head elections among 50 people in Kuala Dua Village, Sungai Raya Subdistrict, Kubu Raya Regency, West Kalimantan. The method of this community service activity is through pre-post steps after the next two weeks to see the effect of the socialization program to minimize abstentions on changes in people's thinking. Will people become more aware of choosing to go to a polling place. The evaluation measuring tools are pre and post-tests in the community. The result of the community service is that there is public awareness to take part in the 2024 elections in presidential, legislative, and regional elections.